THE INFLUENCE OF SELF EFFICACY, BUSINESS CAPITAL, CREATIVITY AND RELIGIOSITY ON THE SUCCESS OF UMKM BUSINESS OF MELINJO CHIPS IN PIDIE DISTRICT - Nufus, Zakiatun; Nizam, Ahmad (Universitas Syiah Kuala, 2024)
This study aims to analyze the effect of self efficacy, business capital, creativity and religiosity on the success of MSMEs of melinjo chips. The sample used in the study amounted to 83 respondents selected using the Proportional Stratified Random Sampling technique. The data analysis technique used is multiple linear regression analysis using SPSS. The results showed that self efficacy, business capital and religiosity partially had a significant effect on business success in MSMEs of melinjo chips in Pidie Regency, but creativity partially had no significant effect on business success in MSMEs of melinjo chips in Pidie Regency. Simultaneously, self efficacy, business capital, creativity, and religiosity affect business success in melinjo chips MSMEs in Pidie Regency. It is hoped that business actors of melinjo chips MSMEs in Pidie Regency can increase selfefficacy, business capital, creativity and religiosity to get business success in their business.